The Effect of Work Environment and Work Motivation on Employee Performance at PT. Bank Syariah Indonesia Branch of Sudirman Bengkulu - Verly Resky Pratama; Suwarni Suwarni; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to examine.whether there is an influence in the work environment and work motivation on employee performance at PT. Bank Syariah Indonesia Bengkulu Sudirman Branch. Employee performance can be assessed as good and good if the implementation is in accordance with the desired goals or is able to meet the needs of a company, but to implement a maximum employee performance we need to pay attention to several aspects that can affect the good or bad of an employee's performance. Such as work environment factors and work motivation that must be considered so that the level of employee performance is maximum and company goals are met. The research sample this time amounted to 60 people from office employees of PT. Bank Syariah Indonesia Bengkulu Sudirman Branch. This research data collection by filling out a questionnaire and the method of analysis is multiple linear regression, correlation test, determination test and hypothesis testing. The results of the regression analysis obtained are Y = 5.553 + 0.267 (X1) + 0.592 (X2) + 3.671. This describes a positive regression direction, meaning that there is a positive influence between X1 (Work Environment) and X2 (Work Motivation) on Y (Employee Performance). If the variables of Work Environment and Work Motivation increase, it will increase Employee Performance. The magnitude of the coefficient of determination is 0.623, this means that the variables of Work Environment (X1) and Work Motivation (X2) have an influence of 62.3% on Employee Performance (Y) while the remaining 37.7% is influenced by other variables not examined. The correlation value is 0.789, this explains that the relationship between the variables of Work Environment (X1) and Work Motivation (X2) on Employee Performance (Y) has a strong relationship. The results of the t test at a significant level of 0.05 explained that partially the Work Environment (X1) and Work Motivation (X2) variables had a significant influence on Employee Performance (Y) at PT. Bank Syraiah Indonesia Bengkulu Sudirman Branch because the value is significantly less than 0.05. The results of the f test at a significant level of 0.05 explain that the variables of Work Environment and Work Motivation have a significant simultaneous influence on employee performance at PT. Bank Syraiah Indonesia Bengkulu Sudirman Branch because the value is significantly less than 0.05.